Influence of ozonation and UV/H2O2 on the genotoxicity of secondary wastewater effluents - Sommaggio, Laís Roberta Deroldo [UNESP]; Mazzeo, Dânia Elisa Christofoletti; Malvestiti, Jacqueline Aparecida; Dantas, Renato Falcão; Marin-Morales, Maria Aparecida [UNESP] (Elsevier, 2024)
The implementation of novel wastewater treatment technologies, including Advanced Oxidation Processes (AOPs) such as ozonation and ultraviolet radiation (UV) combined with hydrogen peroxide (H2O2), can be a promising strategy for enhancing the quality of these effluents. However, during effluent oxidation AOPs may produce toxic compounds that can compromise the water reuse and the receiving water body. Given this possibility, the aim of this study was to evaluate the genotoxic potential of secondary effluents from two different Wastewater Treatment Plants (WWTP) that were subjected to ozonation or UV/H2O2 for periods of 20 (T1) and 40 (T2) minutes. The genotoxic potential was carried out with the Comet assay (for clastogenic damage) and the Micronucleus assay (for clastogenic and aneugenic damage) in HepG2/C3A cell culture (metabolizing cell line). The results of the comet assay revealed a significant increase in tail intensity in the Municipal WWTP (dry period) effluents treated with UV/H2O2 (T1 and T2). MN occurrence was noted across all treatments in both Pilot and Municipal WWTP (dry period) effluents, whereas nuclear buds (NBs) were noted for all Pilot WWTP treatments and UV/H2O2 treatments of Municipal WWTP (dry period). Moreover, the UV/H2O2 (T1) treatment of Municipal WWTP (dry period) exhibited a noteworthy incidence of multiple alterations per cell (MN + NBs). These findings imply that UV/H2O2 treatment demonstrates higher genotoxic potential compared to ozonation. Furthermore, seasonal variations can have an impact on the genotoxicity of the samples. Results of the study emphasize the importance of conducting genotoxicological tests using human cell cultures, such as HepG2/C3A, to assess the final effluent quality from WWTP before its discharge or reuse. This precaution is essential to safeguard the integrity of the receiving water body and, by extension, the biotic components it contains.
Keywords: Advanced oxidation process; Comet assay; Disinfection treatments; HepG2/C3A cells; Micronucleus assay; Wastewater treatment plants